Effect of diesel exhaust inhalation on blood markers of inflammation and neurotoxicity: a controlled, blinded crossover study. (23rd February 2016) - Cliff, Rachel; Curran, Jason; Hirota, Jeremy A.; Brauer, Michael; Feldman, Howard; Carlsten, Chris
Abstract: Context : Epidemiological studies and animal research have suggested that air pollution may negatively impact the central nervous system (CNS). Controlled human exposure studies of the effect of air pollution on the brain have potential to enhance our understanding of this relationship and to inform potential biological mechanisms. Objectives : Biomarkers of systemic and CNS inflammation may address whether air pollution exposure induces inflammation, with potential for CNS negative effects. Materials and methods : Twenty-seven healthy adults were exposed to two conditions: filtered air (FA) and diesel exhaust (DE) (300 μg PM2.5 /m 3 ) for 120 min, in a double-blinded crossover study with exposures separated by four weeks. Prior to and at 0, 3, and 24 h following each exposure, serum and plasma were collected and analyzed for inflammatory cytokines interleukin 6 (IL-6) and tumour necrosis factor alpha (TNF-α), the astrocytic protein S100b, the neuronal cytoplasmic enzyme neuron-specific enolase (NSE), and serum brain-derived neurotrophic factor (BDNF). We hypothesized that IL-6, TNF-α, S100b and NSE would increase, and BDNF would decrease, following DE exposure. Results : At no time-point following exposure to DE was a significant increase in concentration from baseline seen for IL-6, TNF-α, S100b, or NSE relative to FA exposure. Similarly, no significant decrease in BDNF concentration from baseline was seen following DE exposure, relative to FA. Furthermore, the repeated measures ANOVA considered for all time-points and biomarkers revealed no significant time-exposure interaction. Discussion and conclusion : These results suggest that short-term exposure to DE amongst healthy adults does not acutely affect the systemic or CNS biomarkers that we measured.